(untitled) - McFedries, Paul (Hoboken, NJ, 2007)
PowerPoint 2007 Visual Quick Tips provides visual learners with useful and unexpected techniques that can be performed using Microsoft’s robust presentation software.
Keywords: Presentation graphics software.,Phần mềm đồ hoạ trình diễn